2014
DOI: 10.3109/02770903.2014.982287
|View full text |Cite
|
Sign up to set email alerts
|

Atopy as a risk factor for the development of asthma in young recruits

Abstract: Atopy, particularly AR, is a risk factor for the development of new-onset asthma in young adults. Atopy has the highest significant effect in CU where the physical demands are higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…There is a consecutive process in the progression of AR into asthma, as previously demonstrated by a long-term follow-up study (22). This has also been confirmed through a retrospectively study (23,24). The present results showed that the mean duration of AR was longer than asthma in the AR with asthma group, although certain patients reported that asthma was diagnosed earlier than AR.…”
Section: Discussionsupporting
confidence: 88%
“…There is a consecutive process in the progression of AR into asthma, as previously demonstrated by a long-term follow-up study (22). This has also been confirmed through a retrospectively study (23,24). The present results showed that the mean duration of AR was longer than asthma in the AR with asthma group, although certain patients reported that asthma was diagnosed earlier than AR.…”
Section: Discussionsupporting
confidence: 88%
“…We found a total of 29 eligible studies, including 22 cohort studies and 7 case-control studies with a total of 274,489 subjects 6, 7, 8, 9, 11, 12, 15, 16, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45…”
Section: Resultsmentioning
confidence: 99%
“…(2018) 40 SpainCohort of schoolchildren in Castellón, Spain44/128010613–15 years10 years4.05 (1.71–9.60)Age, sex, family history asthma, family history of allergic rhinitis, history of respiratory diseases, breastfeeding, living place, passive smoking, mother's age at time of birth, and pet at homeMoshe et al. (2015) 41 IsraelAll-male Israel Defense Forces (IDF)a1984/128591489118–21 years3 years1.86 (1.57–2.21)SexTormanen et al. (2018) 42 FinlandCohort of infant hospitalized for bronchiolitis18/13839less than 6 months11–13 years4.06 (1.35–12.25)Age, maternal asthma, maternal allergy, parental asthma, paternal allergy, maternal and paternal smokingCarr et al.…”
Section: Resultsmentioning
confidence: 99%